The Surveillance Transceiver Module Design for Improvement of Irradiance Coverage and Image Grayscale Quality - Hsiao-Wen Lee; Bor-Shyh Lin (IEEE Photonics Journal)
Night image quality is gradually emphasized in surveillance industry in past years, and the requirement for the night image definition standards is enhanced. A traditional flashlight-like circularly symmetric light is gradually not suitable for the industry, and the optical design equipped secondary optical elements also encounters the difficulty in space restriction. Package lenses are used for the optical design in this study, mainly replacing the functions of secondary optics and solve the restriction of inadequate internal space of a camera. Meanwhile, the light design of a light-emitting module is proceeded to match the characteristic of a camera image capturing 4:3 or 16:9. Radiant coverage and irradiance efficiency are two parameters to judge the light quality. A new design, under the irradiance efficiency 100%, could enhance the original radiant coverage from 0.366 to 0.825, increasing up to 2.25 times. Besides, the image irradiance uniformity also increases from 0.47 to 0.714, with the increase up to 1.52 times. The package lens design is gradually accepted by international surveillance manufacturers.